2017
DOI: 10.1021/acsami.6b15473
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cellular Internalization: A Bactericidal Mechanism More Relative to Biogenic Nanoparticles than Chemical Counterparts

Abstract: Biogenic synthesis of silver nanoparticles for enhanced antimicrobial activity has gained a lot of momentum making it an urgent need to search for a suitable biocandidate which could be utilized for efficient capping and shaping of silver nanoparticles with enhanced bactericidal activity utilizing its secondary metabolites. Current work illustrates the enhancement of antimicrobial efficacy of silver nanoparticles by reducing and modifying their surface with antimicrobial metabolites of cell free filtrate of Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 59 publications
5
54
0
2
Order By: Relevance
“…Based on the results obtained, BSNP was able to penetrate bacterial membrane more easily than CSNP, which demonstrates the enhancement of antimicrobial efficiency of silver nanoparticles by reducing and modifying their surface with antimicrobial metabolites of cell free filtrate of Trichoderma viride (MTCC 5661) in comparison to citrate stabilized silver nanoparticles. So, this study affirms that biologically synthesized silver nanoparticles coated with antimicrobial metabolites of T. viride were more effective than their chemical counterpart in killing of pathogenic bacteria [131].…”
Section: Toxicity and Challengessupporting
confidence: 70%
“…Based on the results obtained, BSNP was able to penetrate bacterial membrane more easily than CSNP, which demonstrates the enhancement of antimicrobial efficiency of silver nanoparticles by reducing and modifying their surface with antimicrobial metabolites of cell free filtrate of Trichoderma viride (MTCC 5661) in comparison to citrate stabilized silver nanoparticles. So, this study affirms that biologically synthesized silver nanoparticles coated with antimicrobial metabolites of T. viride were more effective than their chemical counterpart in killing of pathogenic bacteria [131].…”
Section: Toxicity and Challengessupporting
confidence: 70%
“…Based on the results obtained, BSNP was able to penetrate bacterial membrane more easily than CSNP, which demonstrates the enhancement of antimicrobial efficiency of silver nanoparticles by reducing and modifying their surface with antimicrobial metabolites of cell free filtrate of Trichoderma viride (MTCC 5661) in comparison to citrate stabilized silver nanoparticles. So, this study affirms that biologically synthesized silver nanoparticles coated with antimicrobial metabolites of T. viride were more effective than their chemical counterpart in killing of pathogenic bacteria [129].…”
Section: Toxicity and Challengessupporting
confidence: 70%
“…Earlier, Noolvi et al (2014) reported cytotoxic and antimicrobial activity of novel azetidine-2-one. Decane, dodecene, undecene, octane, and cetene obtained in the extract form a major part of essential oils, known to show antimicrobial and antioxidative properties (Chouhan et al, 2017;Kumari et al, 2017). Dedecane skeleton containing compounds isolated from marine isolate Penicillium bilaiae MA-267 have shown antifungal properties against plant pathogens (Meng et al, 2014).…”
Section: Analysis Of Bioactive Compounds In Aspergillus Unguis (Ag12mentioning
confidence: 99%